Climate-Growth Response of Cryptomeria japonica Cultivars in Southwestern Japan - Christmas Uchiyama; Wakana A. Azuma; Tsutomu Enoki; Masahiro Takagi; Shin Ugawa; Hiroaki Ishii (Forest Science, 2026)
Understanding how tree growth responds to climate is important for predicting how plantation forests may react to ongoing climate change. In this study, we examined the climate–growth relationships of six Cryptomeria japonica cultivars across five common-garden sites in southwestern Japan using dendrochronological methods. We analyzed 48 years of ring width data to evaluate how monthly and annual temperature and precipitation affect radial growth at site and cultivar levels. Static and moving correlation analyses revealed that late winter to early spring temperatures (February–March) positively influenced radial growth at most sites, likely by facilitating cambial reactivation, while high summer precipitation tended to suppress growth at some sites, possibly through reduced solar irradiance. Precipitation effects were variable across sites, with autumn rainfall showing positive effects at lower-elevation sites. At the cultivar level, early-growth type cultivars tended to show positive temperature responses, while late-growth types showed more variable precipitation responses, though the majority of cultivar-level correlations did not reach statistical significance. Multivariate ordination (PCA) and permutational multivariate analysis of variance (PERMANOVA) on correlation-based response profiles indicated that geographic location was a significant driver of climate-growth response patterns (R 2 = 0.28, p = 0.014), while cultivar type explained a substantial but non-significant proportion of variance (R 2 = 0.23, p = 0.085). These results suggest that local environmental conditions primarily shape climate sensitivity in C. japonica , while genetic provenance provides an additional, non-negligible layer of variation. Our findings underscore the importance of considering both site characteristics and cultivar characteristics in forest management and climate adaptation strategies for C. japonica plantations.

Coordinated seasonal changes in leaf dry mass, leaf photosynthetic rate and vessel formation in diffuse-porous Fagus crenata and ring-porous Quercus crispula trees - Eri Nabeshima; Kayo Kudo; Wakana A. Azuma; Hiroaki Ishii; Ryo Funada (Dendrochronologia, 2026)

Variations in soil compositions and fungal communities are linked to tree composition and understory management - Yuji Tokumoto; Souta Okuyama; Koki Sueyoshi; Harunobu Tanigawa; Rui Ren; Wakana A. Azuma (Landscape and Ecological Engineering, 2026)

Litter decomposition of epiphytic lichens, bryophytes, and vascular plants on the forest floor and canopy in a cool-temperate old-growth forest - Ren Sugimoto; Wakana A. Azuma; Natsuki Komada; Yuya Ogawa (Pedobiologia, 2025)

Radial water transfer from sapwood to inner bark during day time: evidence from diurnal variations in water isotope composition and isotope tracing - Daniel Epron; Yan Xia; Reno Yoshida; Masanori Katsuyama; Wakana A. Azuma; Yoshiko Kosugi; Satoshi Nagai; Masako Dannoura (Trees, 2025)

Effects of host size and substrate types on the distribution of accidental and obligate epiphytes: a case study in a temperate forest of Japan - Natsuki Komada; Wakana A. Azuma; Yuya Ogawa; Chikae Tatsumi (Plant Ecology, 2024)
In forests, the distribution of vascular epiphytes is controlled by various environmental factors such as host tree size and substrate type. However, a few studies focused on temperate forests, despite the growing interest in temperate forests with high diversity of accidental epiphytes. This study examined the distribution of accidental and obligate epiphytes on 8 Cercidiphyllum japonicum (Cercidiphyllaceae) trees in a Japanese temperate forest based on observations of 1,301 epiphyte individuals belonging to 49 species. As predicted, the number of species and individuals of accidental and obligate epiphytes increased with host tree size. While the percentage of accidental epiphyte species increased with the host tree size, the percentage of obligate epiphyte species decreased; however, these changes were not significant for the number of individuals. Consistent with our hypothesis, the major rooting substrates of accidental and obligate epiphytes was different. Accidental epiphytes primarily depend on arboreal soil and, to a lesser extent, on moss, but are absent on tree bark. Contrastingly, obligate epiphytes were most frequently found on moss, followed by bark and arboreal soil. These results highlight the impact of host tree size on the diversity of accidental epiphytes compared to obligate epiphytes, suggesting that the host tree size effects are different between accidental and obligate epiphytes in temperate forests. Additionally, a thick accumulation of arboreal soil is crucial for the establishment of accidental epiphytes.

Legacy over a thousand years: Canopy soil of old-growth forest fosters rich and unique invertebrate diversity that is slow to recover from human disturbance - Ikuyo Saeki; Sho Hioki; Wakana A. Azuma; Noriyuki Osada; Shigeru Niwa; Aino T. Ota; Hiroaki Ishii (Biological Conservation, 2024)

Spawn release of a Sclerophytum soft coral species in Okinawa Island, Japan - Emmeline A. Jamodiong; Tracy D. Tabalanza; Meangeldil A. Azuma-Malsol; Geminne G. Manzano; Agus A. Hakim; Takashi Nakamura; James D. Reimer (Marine Biodiversity, 2024)

Bark traits affect epiphytic bryophyte community assembly in a temperate forest - Shinichi Tatsumi; Takayuki Ohgue; Wakana A. Azuma; Keita Nishizawa (Plant Ecology, 2023)

One large tree crown can be defined as a local hotspot for plant species diversity in a forest ecosystem: a case study in temperate old-growth forest - Wakana A. Azuma; Natsuki Komada; Yuya Ogawa; Hiroaki Ishii; Akira Nakanishi; Yuiko Noguchi; Mamoru Kanzaki (Plant Ecology, 2022)

Improved reproductive performance of tiger tail seahorse, Hippocampus comes, by mysid shrimp fed singly or in combination with other natural food - Shelah Mae A. Buen-Ursua; Teruo Azuma; Katsutoshi Arai; Relicardo M. Coloso (Aquaculture International, 2015)

Interspecific hybridization of fig (Ficus carica L.) and Ficus erecta Thunb., a source of Ceratocystis canker resistance - H. Yakushiji; T. Morita; S. Jikumaru; H. Ikegami; A. Azuma; Y. Koshita (Euphytica, 2012)

Breeding system, colony and population structure in the weaver ant Oecophylla smaragdina - E.A. SCHLÜNS; B.J. WEGENER; H. SCHLÜNS; N. AZUMA; S. K. A. ROBSON; R. H. CROZIER (Molecular Ecology, 2009)
Weaver ants ( Oecophylla smaragdina ) are dominant ants in open forests from India, Australia, China and Southeast Asia, whose leaf nests are held together with larval silk. The species, together with its sole congener O. longinoda , has been important in research on biological control, communication, territoriality and colony integration. Over most of the range, only one queen has been found per colony, but the occurrence of several queens per nest has been reported for the Australian Northern Territory. The number of males mating with each queen is little known. Here we report on the colony structure of O. smaragdina using published and new microsatellite markers. Worker genotype arrays reflect the occurrence of habitual polygyny (more than one queen per colony) in 18 colonies from Darwin, Northern Australia, with up to five queens inferred per colony. Monogyny (one queen per colony) with occasional polygyny was inferred for 14 colonies from Queensland, Australia, and 20 colonies from Java, Indonesia. Direct genotyping of the sperm carried by 77 Queensland queens and worker genotypic arrays of established colonies yielded similar results, indicating that less than half of the queens mate only once and some mate up to five times. Worker genotype arrays indicated that queens from Java and the Northern Territory also often mate with more than one male, but less often than those from Queensland. A strong isolation‐by‐distance effect was found for Queensland samples. The variation uncovered means that O. smaragdina is a more versatile study system than previously supposed.

Calf and shin muscle oxygenation patterns and femoral artery blood flow during dynamic plantar flexion exercise in humans - S. Shimizu; F. Chiarotti; M. Ferrari; A. Kagaya; V. Quaresima; S. Homma; K. Azuma (European Journal of Applied Physiology, 2001)

CYP2C19 genotypes and omeprazole metabolism after single and repeated dosing when combined with clarithromycin - Q. Zhou; I. Yamamoto; T. Fukuda; M. Ohno; A. Sumida; J. Azuma (European Journal of Clinical Pharmacology, 1999)

Analysis of the non-sense mutants of varicella-zoster virus thymidine kinase - T. Suzutani; S. Koyano; M. Saijo; A. Chiba; M. Azuma (Archives of Virology, 1997)